Exploring the role of TikTok for intersectionality marginalized groups: the case of Muslim female content creators in Germany - El Sayed, Fatima; Hotait, Nader (Frontiers in Political Science, 2024)
IntroductionSocial media has become a central part of everyday life, providing spaces for communication, self-expression, and social mobilization. TikTok, specifically, has emerged as a prominent platform for marginalized groups, providing opportunities for activism and representation. However, research falls short in examining the specific role of TikTok for Muslim women in Germany who face intersecting forms of marginalization. This shortcoming reflects a broader lack of research on the experiences of marginalized groups within TikTok’s logics and affordances, and what functions the platform fulfills for these communities. Against this backdrop, this study examines TikTok’s role as a platform for Muslim female content creators in Germany and its broader implications for marginalized communities. Our research is guided by the following questions: (a) What are the main themes and topics that are being brought forward by Muslim women content creators on TikTok? (b) What technical affordances do they use to communicate their content? (c) What functions does TikTok fulfill for Muslim women as an intersectionally marginalized group?.MethodsWe analyze 320 videos from 32 public TikTok accounts identified through snowball sampling. Data collection includes automated web scraping, manual transcription, and qualitative coding. This allows us to identify main topics, video formats, and content types to answer our research questions.ResultsOur findings show that Muslim women produce diverse content on TikTok, ranging from beauty and lifestyle to religious education and social justice. They shape the platform’s functionalities through creative use, while TikTok’s algorithm and virality logic drive creators to blend entertainment with personal content. The hijab emerges as a unique issue, framed within both political and fashion discourses. Overall, TikTok functions as a “third space” where Muslim women challenge mainstream stereotypes and offer alternative interpretations of their identity. While TikTok provides empowerment and visibility, it also exposes Muslim women to hate speech and harassment. The platform provides tools to counter these issues, but the underlying social hierarchies often limit their visibility, making TikTok both a site of empowerment and vulnerability.DiscussionThis study highlights the need for further research into the role of social media for marginalized groups, particularly across platforms, gender, and religion.